Optimization of SiC reinforced Al7039/Cu composites for enhanced thermal conductivity and hardness via response surface methodology - Fetene Teshome Teferi; Kishor Purushottam Kolhe; Assefa Asmare Tsegaw; Samuel Olawale Fatoba (Materials Research Express)
Advancements in engineering technologies are fundamentally driven by the development of superior materials with tailored properties to meet stringent application demands. Metal matrix composites (MMCs) have emerged as essential solutions for such customization. This study presents the synthesis and optimization of Al7039/Cu/SiC MMCs to significantly enhance thermal conductivity and hardness using Response Surface Methodology (RSM). The composites were fabricated by combining aluminum 7039 alloy with high-purity copper (99.98%) and reinforcing them with silicon carbide (SiC) particles. Specimens were efficiently produced using a cost-effective stir casting method with silica sand shell molds using an induction melting furnace. The optimization process involved varying the weight fractions of Al7039 (73%–91%), Cu (4%–12%), and SiC (5%–15%) across 20 experimental runs. Hardness and thermal conductivity were measured using a Rockwell B tester and steady-state linear testing, respectively. Analysis of variance (ANOVA) confirmed that weight fraction variations significantly influenced the measured properties. Statistically significant quadratic models were developed, exhibiting less than 5% variation at a 95% confidence level. Numerical optimization indicated that decreasing Al7039 content while increasing Cu and SiC fractions maximizes thermal conductivity and hardness. This process identified 34 viable solutions, with the optimal composition being 69.22 wt% Al7039, 12 wt% Cu, and 15 wt% SiC. This formulation achieved a thermal conductivity of 167.2 W/m. K and a hardness of 186.1 BHN, corresponding to a desirability score of 0.859 (86%). For robust validation, experiments were meticulously conducted in triplicate using the same procedures and equipment as in the predictive modeling. The experimental results closely matched the predicted values, yielding 169.6 W/m. K and 190.4 BHN improvements of 17.5% and 30% in thermal conductivity and hardness over the base Al7039 alloy, respectively. The optimized Al7039/Cu/SiC composites exhibit significant enhancements over the base alloy, offering excellent properties suitable for demanding applications such as heat sinks, heat exchangers, mold tooling, and critical components in the automotive and aerospace sectors. This study emphasizes the potential of optimized MMCs to efficiently and cost-effectively fulfill advanced engineering requirements, promoting their adoption in innovative technologies.